Theory of questions : erotetics through the prism of its philosophical background and practical applications - Brożek, Anna. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2011)
It is hard to imagine our life without questions. They facilitate orientation in our environment, enable interpersonal communication and make the acquisition of knowledge possible. Questions direct scientific research, are used as research tools and are an important medium of transferring knowledge in teaching. The book is intended as a par excellence philosophical monograph of the theory of questions, presenting the most important erotetic problems, their general background and selected practical applications. It is prepared in all fairness to results acquired in the framework of the logical theories of questions but goes beyond this framework.